ANALISIS TENTANG KETERAMPILAN BERFIKIR SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 1 SUNGAI AMBAWANG - Natalia, Fily Fioleta; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThinking skills or thinking skills are not only important in the world of work, education and training or research. Everyone works in the world of work both in everyday life. In the community or playground, thinking skills are very important to have. Therefore, researchers want to know more about Analysis of the thinking skills of Class VIII Students of the State High School 1 of Sungai Ambawang, Kubu Raya District.The general problem in this study was "How are the Thinking Skills of Class VIII Students of the Ambawang 1 Junior High School in Kubu Raya District? The form of research was survey research involving 49 students of data collection techniques used are direct communication techniques and indirect communication techniques. Data collection tools in the form of questionnaires and interviews for teacher guidance and counseling. Based on the data analysis of thinking skills of class VIII students of SMP N 1 Sungai Ambawang, it was concluded that: (1) students are active when the teacher explains the material during learning (2) students often ask the compilation material given was less clear (3) students can change or change ways thinking in a better direction in accordance with turbulent learning difficulties (4) students can choose material and facilities for complete thinking right to overcome learning difficulties that experience difficulties (5) students draw conclusions about the material that was obtained from the teacher concerned. Keywords: Analysis,Junior High School,Thinking Skills